Does competition for novice borrowers hurt access to finance? An analysis in a context of high risk and low outreach - Verónica Balzarotti; Alejandra Anastasi (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2015)
The lack of access to financial services and to credit in particular is an issue in many developing countries. This paper studies the channels through which new borrowers get access to consumer loans and the effect of repayment data distribution both on that access and on subsequent bank switching by borrowers. We represent such dynamics with a simple model that incorporates different types of lenders and heterogeneity among individuals. The model assumptions are validated against data from the Argentinean banking system. The model yields a set of results that are characteristic of emerging markets: a significant share of the population is excluded from credit, including those who self-exclude, and lender type determines different lending conditions. Additionally, the model shows that distributing loan repayment data, by boosting competition for novice borrowers, may increase the share of the population with no access to credit. Following these findings, we advise focusing on improving available information for unbanked individuals, rather than expanding such information for individuals with a loan payment track record.
Keywords: 330